Cardiac index in adults with repaired tetralogy of Fallot: Are we missing the forest for the trees? - Maria Fadous (Elsevier, 2021)
Background: Many cardiac parameters have been associated with poor outcomes in patients with repaired tetralogy of Fallot (TOF) and significant residual pulmonary regurgitation (PR). However, the utility of cardiac index (CI) in these patients has never been studied. Our study aimed to assess if a low CI is associated with the development of adverse cardiac events in this population and compare it to other established cardiac parameters. Methods: All patients with repaired TOF and significant PR who had a cardiac magnetic resonance imaging (CMR) at our institution were enrolled. CI was measured by CMR and their charts were reviewed for the development of the following outcomes: worsening NYHA class, admission for heart failure, arrhythmias, and sudden cardiac death. Results: Fifty-five patients were included in the study. Median age was 28 years and mean follow-up was 9.5 years. Eighteen patients (32.7%) developed one or more of the predefined outcomes. Their CI was significantly lower compared to patients without adverse events (CI 2.3 vs. 2.8 ​L/min/m2; p-value ​= ​0.0045). CI alone had a better yield in predicting adverse events when compared to the other combined CMR parameters (AUC 0.78 vs 0.61). Patients with a CI ​< ​2.4 had a 74.3% cumulative probability of developing adverse cardiac events at 10 years compared to 22.4% in patients with a CI ​≥ ​2.4 (p-value<0.0001). Conclusion: In adults with repaired TOF and significant residual PR, CI appears to be the best predictor of midterm adverse cardiac events. Whether it can be used for timing of pulmonary valve replacement remains to be studied.